Improving Beginning Text Writing Skills through the Montessori Method in Early Childhood in the Pasar Baru Environment of Bima City - Noor Leha; Ulfa Widayati; Akhmad Syakir; Jamiatul Hamidah; Susan Susan (JINoP (Jurnal Inovasi Pembelajaran), 2026)
Background: Children living in socially and economically vulnerable environments often experience limited access to literacy support, which may affect the development of their early writing skills. In the Pasar Baru area of Kota Bima, many elementary school-aged children demonstrated low confidence, inconsistent learning behaviors, and limited writing abilities during preliminary observations. Objectives: This study aimed to analyze the effectiveness of the Montessori approach in improving early writing skills among elementary school-aged children in the Pasar Baru area of Kota Bima. Methods: This study employed a mixed-methods approach integrating quantitative and qualitative data. The participants consisted of 12 children aged 6–9 years selected using purposive sampling techniques. Data were collected through observations, interviews, documentation, and pretest–posttest writing assessments. The intervention was conducted through Montessori-based literacy activities emphasizing sensory learning, tracing exercises, concrete educational materials, and guided writing practice. Results: The findings revealed significant improvement in children’s writing performance after the intervention. The average writing score increased from 8.25 in the pretest assessment to 13.83 in the posttest assessment. Children also demonstrated improved learning engagement, confidence, motivation, and independence during literacy activities. The use of multisensory learning materials such as sandpaper letters, movable alphabets, and tracing activities positively contributed to children’s visual-motor coordination and grapheme recognition. Conclusions: The Montessori approach can function as an effective and contextual literacy intervention for improving early writing skills among children living in nonformal and socially vulnerable learning environments.